Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To determine if two functions are inverses of each other, we need to check if their compositions [tex]\( F(G(x)) \)[/tex] and [tex]\( G(F(x)) \)[/tex] both simplify to [tex]\( x \)[/tex].
Given the functions:
[tex]\[ F(x) = \sqrt{x} + 3 \][/tex]
[tex]\[ G(x) = (x - 3)^2 \][/tex]
Step-by-step solution:
1. Compute the composition [tex]\( F(G(x)) \)[/tex]:
[tex]\( G(x) = (x - 3)^2 \)[/tex]
Now substitute [tex]\( G(x) \)[/tex] into [tex]\( F(x) \)[/tex]:
[tex]\[ F(G(x)) = F((x - 3)^2) = \sqrt{(x - 3)^2} + 3 \][/tex]
Since [tex]\(\sqrt{(x - 3)^2} \)[/tex] is [tex]\(|x - 3|\)[/tex]:
[tex]\[ F(G(x)) = |x - 3| + 3 \][/tex]
For [tex]\( x \geq 3 \)[/tex], [tex]\(|x - 3| = x - 3\)[/tex], so:
[tex]\[ F(G(x)) = x - 3 + 3 = x \][/tex]
For [tex]\( x < 3 \)[/tex], [tex]\(|x - 3| = -(x - 3) = 3 - x\)[/tex], so:
[tex]\[ F(G(x)) = 3 - x + 3 = 6 - x \][/tex]
Therefore:
[tex]\[ F(G(x)) = |x - 3| + 3 \][/tex]
2. Compute the composition [tex]\( G(F(x)) \)[/tex]:
[tex]\( F(x) = \sqrt{x} + 3 \)[/tex]
Now substitute [tex]\( F(x) \)[/tex] into [tex]\( G(x) \)[/tex]:
[tex]\[ G(F(x)) = G(\sqrt{x} + 3) = (\sqrt{x} + 3 - 3)^2 \][/tex]
Simplifying inside the parentheses:
[tex]\[ G(F(x)) = (\sqrt{x})^2 \][/tex]
Which simplifies to:
[tex]\[ G(F(x)) = x \][/tex]
From the compositions, we observe the following:
[tex]\[ F(G(x)) = |x - 3| + 3 \quad \text{and} \quad G(F(x)) = x \][/tex]
Since [tex]\( F(G(x)) \neq x \)[/tex] for all [tex]\( x \)[/tex] (specifically because of the absolute value operation), the composition [tex]\( F(G(x)) \)[/tex] does not result in [tex]\( x \)[/tex] consistently.
Therefore, the correct answer is:
[tex]\[ \text{A. No, because the composition does not result in an answer of } x. \][/tex]
Given the functions:
[tex]\[ F(x) = \sqrt{x} + 3 \][/tex]
[tex]\[ G(x) = (x - 3)^2 \][/tex]
Step-by-step solution:
1. Compute the composition [tex]\( F(G(x)) \)[/tex]:
[tex]\( G(x) = (x - 3)^2 \)[/tex]
Now substitute [tex]\( G(x) \)[/tex] into [tex]\( F(x) \)[/tex]:
[tex]\[ F(G(x)) = F((x - 3)^2) = \sqrt{(x - 3)^2} + 3 \][/tex]
Since [tex]\(\sqrt{(x - 3)^2} \)[/tex] is [tex]\(|x - 3|\)[/tex]:
[tex]\[ F(G(x)) = |x - 3| + 3 \][/tex]
For [tex]\( x \geq 3 \)[/tex], [tex]\(|x - 3| = x - 3\)[/tex], so:
[tex]\[ F(G(x)) = x - 3 + 3 = x \][/tex]
For [tex]\( x < 3 \)[/tex], [tex]\(|x - 3| = -(x - 3) = 3 - x\)[/tex], so:
[tex]\[ F(G(x)) = 3 - x + 3 = 6 - x \][/tex]
Therefore:
[tex]\[ F(G(x)) = |x - 3| + 3 \][/tex]
2. Compute the composition [tex]\( G(F(x)) \)[/tex]:
[tex]\( F(x) = \sqrt{x} + 3 \)[/tex]
Now substitute [tex]\( F(x) \)[/tex] into [tex]\( G(x) \)[/tex]:
[tex]\[ G(F(x)) = G(\sqrt{x} + 3) = (\sqrt{x} + 3 - 3)^2 \][/tex]
Simplifying inside the parentheses:
[tex]\[ G(F(x)) = (\sqrt{x})^2 \][/tex]
Which simplifies to:
[tex]\[ G(F(x)) = x \][/tex]
From the compositions, we observe the following:
[tex]\[ F(G(x)) = |x - 3| + 3 \quad \text{and} \quad G(F(x)) = x \][/tex]
Since [tex]\( F(G(x)) \neq x \)[/tex] for all [tex]\( x \)[/tex] (specifically because of the absolute value operation), the composition [tex]\( F(G(x)) \)[/tex] does not result in [tex]\( x \)[/tex] consistently.
Therefore, the correct answer is:
[tex]\[ \text{A. No, because the composition does not result in an answer of } x. \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.